SURVIVAL AND GROWTH OF CULTIVATED FISHES IN ASSAM PONDS - Lakshmanan, M A V; Bhuyan, B R; Radhakrishnan, S; Babu, N (Indian Journal of Fisheries, 2011)
INFORMATION on the natural survival and growth of fishes is a basic necessity to consider improvement measures in fish culture. In India, however, such useful information on a regional basis is at present very limited and inadequate. It is a well-known fact that the productivity of fish in natural waters is dependent on a wide variety of physical, chemical and biological conditions of the water. Hence, it is essential to make a thorough study of these water conditions under which fish are cultured, in order to elucidate the causative factors involved and control survival and growth. Though such a detailed study for a vast region has its own limitations, an attempt was made by the Pond Culture Research Unit of the Central Inland Fisheries Research Institute at Joysagar, to gather the essential basic data, viz., data on natural survival, growth and production of the three species in normally prepared typical fish ponds of Assam, without fertilisation and supplementary feeding of fish. This paper embodies the results of investigations carried out during the period 1960 to 1963.